Pengaruh Harga Terhadap Keputusan Pembelian Maksker Garnier - Firman Gazali (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2020)
Currently, many manufacturers produce and sell various brands of face masks, so that makes consumers have many choices before deciding to buy a face mask that is practical application and of course has an affordable price. The purpose of this study is the Effect of Prices on Garnier Maksker Purchasing Decisions The population in this study is consumers in Namlea district who use Garnier Masks. The sample in this study was 100 people who bought garnier masks were taken by purposive sampling. Data collection is done by using a questionnaire. The data analysis method used is SPSS version 21. The results of multiple regression analysis are Y = 0.307 X1 + 0.176 X2 + 0.137 X3 The independent variable that most influences the dependent variable is the Variable Product Variable (0.307), followed by the Price variable (0.176). T test results show that all independent variables (product and price variations) have a significant positive effect on the dependent variable (purchasing decisions) where all independent variables obtain a t value greater than t table with a sig level of less than 0.05. And the coefficient of determination (R Square) obtained by 0.603 this means that 60.3% of purchasing decisions can be explained by product variation variables, prices, while the remaining 39.7% is influenced by other variables not examined in this study.